Development of a rapid condition assessment tool for CHB wall-type residential buildings under earthquake loading - Tuppil, Camille G.
This research describes the process of developing a rapid visual pre-earthquake structural assessment tool for CHB Wall-Type residential buildings built locally in the Philippines. The tool provides a structural score that describes the overall safety of a structure in the event of an earthquake. The structural score is composed of the Basic Score, Modifiers, and a Damage Modification Factor which represents the capacity of the structure and the effects of existing damage. The scores were derived from computational fragility curves of CHB houses. By comparing the Final Score to a Cut-Off Score, the building can be judged as safe or recommended for more detailed evaluation. Recommended Cut-Off scores were calculated. The tool was successfully validated using comparisons with assessments to results of a shaking table test done by JICA in 2011. Using this tool, the number of structures that will undergo detailed assessment (level 2 evaluation) will be reduced.